PENGUJIAN PENGARUH STRUKTUR UTANG DAN PROFITABILITAS TERHADAP PERTUMBUHAN LABA DIMODERASI OLEH KEPEMILIKAN MANAJERIAL - Adityaputra, Stephanus Andi (COMPETITIVE, 2024)
Profit serves as the main indicator in assessing a company's financial performance. Because profit growth cannot be guaranteed, it is necessary to carry out an analysis to assess the level of profit growth. In this context, analysis of debt structure, profitability and profit growth is very important for stakeholders to understand the company's financial performance. This research aims to evaluate and identify the impact of Capital Structure and Profitability on Profit Growth. The research sample was determined using a purposive sampling technique to produce 45 samples from construction subsector companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. The research data was then analyzed using Simple Linear Regression Analysis and Moderated Regression Analysis (MRA) using IBM SPSS Statistics 25 to process data. Based on the research results, it is concluded that Capital Structure as measured using the Debt to Equity Ratio (DER) and Profitability as measured using Return on Assets (ROA) have a positive and significant influence on Profit Growth. Apart from that, Managerial Ownership is unable to moderate the influence of Capital Structure or Profitability on Profit Growth.